2007
DOI: 10.1007/s10681-007-9631-z
|View full text |Cite
|
Sign up to set email alerts
|

Freezing tolerance of selected perennial ryegrass (Lolium perenne L.) accessions and its association with field winterhardiness and turf traits

Abstract: Many winter stresses aVect the ability of a perennial grass to overwinter in cold, temperate climates. Freezing tolerance is one of the major component traits aVecting winterhardiness. Although eVective freezing tolerance assessment procedures have long been available for perennial ryegrass (Lolium perenne L.), no work has been done to characterize plant collections in the United States that may possess novel variation for freezing tolerance and winterhardiness. In this study, 21 accessions sampled from a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…The highest percentage of dry matter was recorded in these two months, and can be related to diversity and genetic variability of species in pastures and reduced cold tolerance that have experienced some cultivars of Lolium perenne L. species, principal component of pastures (Hulke et al, 2008). In a scenario of changing in the climate conditions, where plants grasses are subjected to higher temperatures during the growing season, species and cultivars reduce their ability to withstand cold conditions, which generate in stress but induce an increased cold resistance by increasing the cell walls, and thereby, the dry matter production (Thorsen and Höglind, 2010).…”
Section: Forage Qualitymentioning
confidence: 93%
“…The highest percentage of dry matter was recorded in these two months, and can be related to diversity and genetic variability of species in pastures and reduced cold tolerance that have experienced some cultivars of Lolium perenne L. species, principal component of pastures (Hulke et al, 2008). In a scenario of changing in the climate conditions, where plants grasses are subjected to higher temperatures during the growing season, species and cultivars reduce their ability to withstand cold conditions, which generate in stress but induce an increased cold resistance by increasing the cell walls, and thereby, the dry matter production (Thorsen and Höglind, 2010).…”
Section: Forage Qualitymentioning
confidence: 93%
“…It has been demonstrated that WH depends on the ability of plants to survive low temperatures, extreme temperature fluctuation, wind desiccation, ice nucleation, and snow mold infection (Humphreys, 1989). The intensity of each factor depends on the year and the location, and it is commonly agreed that frost tolerance (FT) is the main component of WH and one of the best indicators of plant ability to survive harsh winter conditions (Humphreys, 1989;Hulke et al, 2008). The plant species growing in temperate regions can acquire FT through exposure to low, non-lethal temperatures, a phenomenon known as cold acclimation (CA).…”
Section: Introductionmentioning
confidence: 99%
“…Injury caused by low temperatures affects the survival of different species and quality of the stand in the spring (Gusta et al, 1980;Karnok and Beard, 1983;Bertrand et al, 2013). Responses of turfgrasses to local microclimates will be affected by topography, elevation, southern exposure, or shading from buildings or trees (Hulke et al, 2008;Bertrand et al, 2013). Microclimatic conditions can offset or accentuate the effects of climate for a specific region and illustrate the complex nature of the interactions in developing general statements about the impact of climate change.…”
Section: Temperature Impactsmentioning
confidence: 99%